Verbal and Non Verbal Signs in the First Episode of Webtoon Orange Marmalade - Bella Prabasari, Desak Putu; Weddha Savitri, Putu; Shanti Sari Dewi, A.A. Sg. (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p14, 2018)
This study is entitled Verbal and Nonverbal signs in the first episode of webtoon Orange Marmalade. This study mainly focuses on the analysis of signifiers and the signified of the verbal and nonverbal signs and their relationship in creating an event in the first episode of webtoon Orange Marmalade. Semiotic theory by Saussure’s was applied to analyze the first problem about signifying of the verbal and nonverbal signs while McCloud’s theory of relationship in comic was applied to analyze the second problem. Qualitative method was applied in the analysis of this study. The source of data was taken from the first episode of Webtoon entitled Orange Marmalade by using documentation method. The data were presented descriptively in the form of table and diagram. All types of signs found in the first episode of webtoon entitled Orange Marmalade consist of signifier and signified by verbal and nonverbal sign. The analysis reveals that the meaningful event is created by the relationship between verbal and nonverbal signs comprised in each panel within a page of the webtoon. The analysis also shows that both verbal and nonverbal signs support each other in conveying the idea.